Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Minyak Goreng - Lu'lu Ul Maknunah (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2022)
Cooking oil is one of the ingredients in the kitchen that must be present. In making a decision to purchase cooking oil, there are several things that buyers pay attention to. In this study, researchers tried to find out whether product quality and price are the two things that influence the purchasing decision of cooking oil. This research was conducted on 35 respondents in the stalls Veteran Street, Blitar City. The tests used in analyzing the results of the questionnaire were classical assumption test and hypothesis testing. The results obtained from the questionnaire data analysis were obtained sig value. of 0.011 and 0.013 respectively for the independent variable product quality and the independent variable price. The F test shows the value of sig. 0.001 for the simultaneous effect of the independent variable on the dependent variable. The conclusion based on the results of the analysis of hypothesis testing was either partially or simultaneously, the independent variable of product quality and the independent variable of price influence the purchasing decision of cooking oil.